Retrospective investigation of children presented with febrile convulsion (Annals of Medical Research, 2024)
Aim: In this study, we aimed to determine the characteristics of patients admitted with the diagnosis of febrile convulsion (FC) and to evaluate the most common diagnosis and the most frequent months of presentation.Materials and Methods: A total of 172 children who were admitted to the pediatric emergency unit in the last one year due to FC and were admitted for observation were included in the study. The age range of the children included in the study was 5 months - 6 years (72 months). Patients were analyzed in terms of age, gender, diagnosis at presentation, type of FC, month of presentation, whether brain tomography was performed, sodium level, CRP level, white blood cell (WBC) count, and glucose level. SPSS (Statistical Package for Social Sciences) for Windows 22.0 program was used for statistical analysis.Results: The median age of the patients was 20 (11-34) months and 58.7% were male. Upper respiratory tract infections were the most common cause of convulsions with 72.7%. Acute gastroenteritis followed with 20.9%. Simple febrile convulsion was present in 89.5% of cases. Brain tomography was required in 33.1% of the patients admitted due to FC. The most common month of presentation was November with 16.3%. Mean WBC level was 13.4±6.0 (x103/μL), mean CRP level was 24.2±35.3 (mg/L), mean Glucose level was 117±29.8 (mg/dL), mean Sodium level was 137±13.9 (mmol/L).Conclusion: In the management of this condition, which is uncomplicated and has no long-term effects in most patients, it is important to avoid unnecessary examinations and to provide accurate information to families.
Keywords: Fever; Convulsion; Children